KUALITAS WARNA PENCELUPAN EKSTRAK KULIT BUAH MANGGIS BERDASARKAN KONSENTRASI WAKTU PERENDAMAN DAN JUMLAH MORDAN KAPUR TOHOR (CACO3) PADA BENANG SUTERA - Farihah Farihah; Riza Risnawati (Universitas Negeri Medan, 2013)
ABSTRACTThis study aims to determine the color quality from the results of mangosteen dyeing extracts rind on silk yarn based on the time of immersion and the amount of lime tahor (CaCO3). A method used is an experimental method that uses 5 x 2 factorial designs with 10 combinations was performed using the formula one-way ANOVA. Based on the calculation of analysiss, groups using lime mordant 16 g / liter had a higher mean than the group means using lime mordant 8 g / liter. For the average lowest value found in the group with soaking for 1 hour by using lime mordant 8 g / liter. As for the average of the highest values found in the group with soaking for 18 hours by using a mordant lime 16 g / liter. As for the hypothesis test concluded that there was no significant difference in the color quality of the dyeing mangosteen peel extract as a natural dye using silk thread is based on the time of immersion and the amount of mordant lime (CaCO3) which is diffirent. All in all, the longer the soaking time concentration rind mangosteen will produce color and sparkling despite getting older did not differ significantly and the use of lime tahor amount that will more evenly produce more color and more concentrated. Kata Kunci : Ekstrak kulit buah manggis, konsentrasi, benang sutera.